Pemrosesan Data Sisi Klien Menggunakan Rakitan Web di Aplikasi Rendering Sisi Server - Elsen, Rickard; Wijaya, Tryana Hadi; Setiawan, Ridwan (Al-Mantiq, 2023)
Nowadays, web developers are required to choose between Single-Page Application (SPA) or Server-Side Rendering (SSR). Both types of web applications have their own advantages and disadvantages. Currently, most developers use Javascript to be able to perform computations on the client side even though the web application built is SSR. Scripts in Javascript are compiled by the web browser before the functions in the script can be used by the user. These functions will be executed on the client side so that computation does not need to be done on the server side. Since the use of Javascript is by sending source code to the client to be compiled and executed, WebAssembly (Wasm) allows the server to send those functions in precompiled binary files. The functions contained in the binary can be used by web applications and will be executed on the client side, so the browser doesn't need to compile it first to use existing functions. In this paper, we utilize Wasm to perform data processing on the client side of the SSR web application by performing some queries to preserved data.